The Effect of Cadres Training on Competence Of Tuberculosis Health Cadres At The Muntok Health Center In West Bangka Regency - Rudini Rudini; Helda Helda; Meiristia Qomariah (Jurnal EduHealth, 2023)
Tuberculosis remains a significant problem in Indonesia, and the country has set goals to eliminate the disease by 2030 and end the tuberculosis epidemic by 2050. However, the Tuberculosis Surveillance System evaluation in West Bangka Regency has revealed that the involvement of health cadres in community-based tuberculosis prevention and control has not been fully effective. Additionally, the CDR indicator, which measures the performance of tuberculosis control, was still very low at 18.7% in 2022, far below the target of 54%. To address these issues, a research was conducted at the Muntok Health Center in West Bangka Regency, aiming to enhance the knowledge and skills of health cadres in community-based tuberculosis prevention and control. The research design employed was a Pre-Experimental with the form of one-group pretest-posttest design, and a total of 27 individuals were sampled for the research. The research was conducted from November 2022 to January 2023. The intervention in this research consisted of training sessions that utilized lecture/presentation methods, discussions, and role-play activities. Questionnaires were used for data collection, and the data were analyzed through univariate and bivariate analyses using the Paired t-test and Mc-Nemar test. The participants predominantly consisted of females (100%), with a majority having a senior high school education (51.8%). Most of them had prior experience as health cadres (77.8%) and fell within the age range of 36-45 years (48.2%). The average knowledge score before the training was 9.3 (95% CI= 8.1-10.4), which significantly increased to 17.2 (95% CI= 16.4-17.9) after the training (p-value = 0.0001). In terms of skills, only 5 participants were deemed skilled before the training, but this number increased to 19 after the training. However, the statistical analysis showed no significant effect of the training on participant’' skills before and after the training (p-value = 0.0005). Overall, the training conducted successfully increased the average knowledge of health cadres and had some impact on their skills at the Muntok Health Center in Bangka Barat Regency. It is important to optimize the role of knowledgeable and skilled health cadres, so that they can effectively contribute to community-based tuberculosis prevention and control, in collaboration with other healthcare professionals.